Análise de indicadores socioeconômicos em unidades de produção agropecuária do tipo familiar - Dettmer, Carlos Alberto (2014)
Family farming has been a constant focus of study given its importance as a producer of food and especially the social function assigned to it. The search for grants for construction of indicators that are relevant in the management of agricultural production units is constant. Objective of this paper is to identify and analyze the main socioeconomic indicators in the management of agricultural production units of family type in agrarian reform settlement. This is a qualitative and quantitative research with exploratory and descriptive. As for the technical procedures, or ténicas data collection, the research strategy, utilized, was lifting the field through interviews. We adopted also exploratory, descriptive and documentary studies. MS - 59 in the sample of rural households Teijin, New Andradina settlement were interviewed. Main activities are operated by families settled include: milk production, practiced in 69.6% of the PSUs, beef 6.8%, and the production of horticultural, cassava. Also part time activity is highlighted, being practiced in 76.27% of the PSUs. Each PSU has an area of 14.52 hectares for exploration. The main sources of household income are dairy farming and the practice part time. The family succession appears as a leading indicator that compromises the sustainability of UPA's medium and long term